Disparities in Pollution Capitalization Rates: The Role of Direct & Systemic Discrimination - Joshua Graff Zivin; Gregor Singer (CESifo GmbH, 2025)
We examine how exogenous changes in exposure to air pollution over the past two decades have altered the disparities in home values between Black and White homeowners. We find that air quality capitalization rates are significantly lower for Black homeowners. In fact, they are so much lower that, despite secular reductions in the Black-White pollution exposure gap, disparities in housing values have increased during this period. An exploration of mechanisms suggests that roughly 60% of this difference is the result of direct discrimination while the remaining 40% can be attributed to systemic discrimination.
Keywords: Q51; R30; J15; 330; house prices; environmental justice; air pollution; race; discrimination